MAP1981c, a Putative Nucleic Acid-Binding Protein, Produced by Mycobacterium avium subsp. paratuberculosis, Induces Maturation of Dendritic Cells and Th1-Polarization - Kim, Woo Sik; Shin, Min-Kyoung; Shin, Sung Jae (Frontiers in Cellular and Infection Microbiology, 2018)
Mycobacterium avium subsp. paratuberculosis (MAP) is the causative pathogen of chronic granulomatous enteropathy (Johne’s disease) in animals, and has been focused on its association with various autoimmune diseases in humans, including Crohn's disease. The discovery of novel mycobacterial antigens and exploring their role in host immunity can contribute to the advancement of effective defense strategies including vaccines and diagnostic tools. In a preliminary study, we identified cellular extract proteins of MAP that strongly react with the blood of patients with Crohn's disease. In particular, MAP1981c, a putative nucleic acid-binding protein, showed high expression levels and strong reactivity to IgG and IgM in the sera of patients. Here, we investigated the immunological features of MAP1981c and focused on its interaction with dendritic cells (DCs), confirming its immunomodulatory ability. MAP1981c was shown to recognize Toll-like receptor (TLR) 4, and induce DC maturation and activation by increasing the expression of co-stimulatory (CD80 and CD86) and MHC class I/II molecules and the secretion of pro-inflammatory cytokines (IL-6, IL-1β, and TNF-α) in DCs. This DC activation by MAP1981c was mediated by downstream signaling of TLR4 via MyD88- and TRIF-, MAP kinase-, and NF- κB-dependent signaling pathways. In addition, MAP1981c-treated DCs activated naïve T cells and induced the differentiation of CD4+ and CD8+ T cells to express T-bet, IFN-γ, and/or IL-2, but not GATA-3 and IL-4, thus indicating that MAP1981c contributes to Th1-type immune responses both in vitro and in vivo. Taken together, these results suggest that MAP1981c is a novel immunocompetent antigen that induces DC maturation and a Th1-biased response upon DC activation, suggesting that MAP1981c can be an effective vaccine and diagnostic target.